Interoception, alexithymia, and anxiety among individuals with alcohol use disorder - Wiśniewski, Paweł; Jakubczyk, Andrzej; Trucco, Elisa M.; Kobyliński, Paweł; Suszek, Hubert; Zaorska, Justyna; Rydzewska, Małgorzata; Kopera, Maciej (Frontiers in Psychiatry, 2023)
Background: Interoception (i.e., the ability to recognize bodily signals), alexithymia (i.e., the inability to recognize emotional states) and negative affect (i.e., unpleasant feelings such as anxiety) have been associated with alcohol use disorder (AUD). Previous research suggests that interoception may underlie alexithymia, which in turn may be associated with negative affectivity. However, this remains to be empirically tested. This study investigates whether alexithymia mediates the association between interoception and anxiety and whether this association differs across individuals with AUD and a healthy control (HC) comparison group.The AUD group consisted of 99 participants enrolled in an 8-week abstinence-based inpatient treatment program. The HC group included 103 healthy individuals. The heartbeat counting task (HCT) was used to assess interoception (cardiac interoceptive accuracy). The Toronto Alexithymia Scale (TAS-20) was used to assess alexithymia. The Brief Symptom Inventory (BSI) was used to assess anxiety.The moderated mediation model with interoception as the predictor, alexithymia as the mediator, and negative affect (i.e., state anxiety) as the dependent variable was tested. The analysis showed that the conditional indirect effect of interoception on anxiety via alexithymia was significant for individuals with AUD (ab = -0.300, bootstrap 95% CI = [-0.618, -0.088]), as well as for HCs (ab = -0.088, bootstrap 95% CI = [-0.195, -0.014]); however, the conditional indirect effect significantly differed across HCs and individuals with AUD. Namely, the mediated effect was greater among individuals with AUD compared to the HC group.The results suggests that interoceptive impairment contributes to greater negative affect (i.e., state anxiety) via alexithymia especially for individuals with AUD. Improving emotion recognition via therapeutic methods focused on strengthening interoceptive abilities could improve outcomes for individuals receiving treatment for AUD.